A consultoria legislativa da Câmara dos Deputados à luz do princípio da transparência: perspectivas sobre o papel do órgão e a divulgação de seus trabalhos - Fabiana Miranda Prestes (2024)
This study sought to understand how the studies produced by the Legislative Consultancy of the Chamber of Deputies (Conle) are disseminated. The Conle is a technical advisory body available to Federal Deputies, the Board of Directors, Committees and the Presidency of the House. Despite the large volume of work produced by the body, which includes studies, technical notes and descriptive notes, only a small portion of these works are published through the Chamber of Deputies Portal. To understand how this disclosure takes place and what the criteria are for publicizing or keeping these documents secret, a case study was carried out on the body, focusing on the years 2020, 2021 and 2022, and on the work produced by the area of Environment and Environmental Law, Territorial Organization, Urban and Regional Development (area XI) of Conle in the year 2021. Initially, the study carried out here sought to understand the norms and foundations associated with restricting the dissemination of Conle's work, comparing them with the constitutional, normative and theoretical provisions that underlie the wide circulation of technical information in the legislative process. Subsequently, an exploratory analysis was carried out regarding the dissemination of Conle studies on the Chamber of Deputies Portal. It was found that the published studies were the result of the consultants' initiative or linked to a specific specialization project at the House. The conclusions of this study indicate the need to rethink the confidentiality applicable to purely informative documents produced by Conle, given the need to justify the laws and the role that this body plays in reducing informational asymmetries.